Factors Affecting The Participation of Tammekkawatang Grazing Pasture Regency of Pinrang, South Sulawesi - Andi fitri Faharuddin; Azizah Siti; Wisaptiningsih Umi (Hasanuddin University, 2020)
Participation is an important component in the process of empowering a community, especially farmers. In this process, the community is supported to improve prosperity independently. The role of institutions as facilitators who accompany the empowerment process. In principle, the community is the perpetrator and the subject of development. it requires Information related factors that influence the participation of breeders in the Empowerment program so that the preparation of empowerment strategy can be more directional and the result will be more optimal. This research aims to determine the factors affecting the participation of farmers in the grazing Empowerment program as a reference to create a more interesting empowerment program. The research was conducted in the Pinrang district of Suppa and Mattirobulu sub-districts with samples of 147 breeders. The collection of research data is done using questionnaires and then carried out data using the SmartPLS statistics tool. The result of this research is known that the factors affecting the participation of farmers are the motivation and stakeholder role.